2023
DOI: 10.3390/f14040821
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study: Micropropagation Using Five Types of Chelated Iron and the Subsequent Acclimation of Blue Honeysuckle (Lonicera caerulea var. kamtschatica Sevast.)

Abstract: Blue honeysuckle (Lonicera caerulea var. kamtschatica Sevast.) is a valuable berry crop with a unique biochemical composition. It is rich in vitamins, minerals, and biologically active substances. Different species and cultivars of honeysuckle require different cultivation conditions in the field of accelerated reproduction in vitro. Taking into account the high clonal replication potential of the plant, we conducted research on the chelated-iron form’s influence on the micropropagation productivity of the blu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…The optimal concentration of iron in the medium is 70–100 µM, in the form of iron(II) sulfate heptahydrate (FeSO 4 ·7H 2 O), a commonly used salt. However, Fe is not soluble and is rarely accessible to plants; therefore, it is used more effectively in a Fe chelate form, as ferric ethylenediaminetetraacetic acid (FeEDTA) chelated from FeSO 4 , or in a directly chelated form, as ethylenediamine di-2-hydroxyphenyl acetate ferric (FeEDDHA), among others [ 54 ]. The chelated form FeEDDHA is more stable at different pH levels and has shown relevant results for different species evaluated, including date palm [ 55 ], walnut [ 56 ], and hazelnut [ 57 ].…”
Section: Major Aspects Of Plant Regenerationmentioning
confidence: 99%
“…The optimal concentration of iron in the medium is 70–100 µM, in the form of iron(II) sulfate heptahydrate (FeSO 4 ·7H 2 O), a commonly used salt. However, Fe is not soluble and is rarely accessible to plants; therefore, it is used more effectively in a Fe chelate form, as ferric ethylenediaminetetraacetic acid (FeEDTA) chelated from FeSO 4 , or in a directly chelated form, as ethylenediamine di-2-hydroxyphenyl acetate ferric (FeEDDHA), among others [ 54 ]. The chelated form FeEDDHA is more stable at different pH levels and has shown relevant results for different species evaluated, including date palm [ 55 ], walnut [ 56 ], and hazelnut [ 57 ].…”
Section: Major Aspects Of Plant Regenerationmentioning
confidence: 99%
“…After the first study that focused on shoot proliferation of blue honeysuckle (L. caerulea and L. caerulea var. edulis) [24], subsequent research studies have demonstrated the micropropagation efficiency of blue honeysuckle is influenced by genotypes [25], base medium compositions (MS, 3/4 MS, 1/4 MS, and MS supplemented with wheat starch) [24,[26][27][28], plant growth regulators (6-BA and thidiazuron + IAA) [25,29], chelated irons (FeNaEDDHA, Fe(III)-EDTA, Fe(III)-DTPA, Fe(III)-EDDHA, Fe(III)-HEDP, and Fe(II)-HEDP) [27,28], and culture temperatures [24]. To the best of our knowledge, there have been no reports about plant regeneration through the ISE pathway on blue honeysuckle.…”
Section: Introductionmentioning
confidence: 99%